2018
DOI: 10.1111/adb.12631
|View full text |Cite
|
Sign up to set email alerts
|

Face validity of a pre‐clinical model of operant binge drinking: just a question of speed

Abstract: Binge drinking (BD) is often defined as a large amount of alcohol consumed in a 'short' period of time or 'per occasion'. In clinical research, few researchers have included the notion of 'speed of drinking' in the definition of BD. Here, we aimed to describe a novel pre-clinical model based on voluntary operant BD, which included both the quantity of alcohol and the rapidity of consumption. In adult Long-Evans male rats, we induced BD by regularly decreasing the duration of ethanol self-administration from 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 38 publications
3
42
1
1
Order By: Relevance
“…In summary, preclinical evidence show that CBD may be of strong therapeutic interest in AUD and could have a significant action on drinking levels in human subjects with AUD, since it is effective on different aspects of the disease (intake, motivation, relapse, anxiety, and impulsivity). However, it should be noted that there are no available data on CBD efficacy in more relevant animal models of AUD, such as binge drinking models (Jeanblanc et al, 2018; Jeanblanc et al, 2019) or in models that use more chronic exposure to ethanol and behaviors linked to addiction (loss of control over intake, compulsive use of ethanol, increased motivation) (Meinhardt and Sommer, 2015). Thus, whether CBD is effective in animal models such as the postdependent state, in which rats drink ethanol for months and are exposed to ethanol vapors in order to induce dependence, is unknown.…”
Section: Cannabidiol For Reducing Alcohol Drinking Levelsmentioning
confidence: 99%
“…In summary, preclinical evidence show that CBD may be of strong therapeutic interest in AUD and could have a significant action on drinking levels in human subjects with AUD, since it is effective on different aspects of the disease (intake, motivation, relapse, anxiety, and impulsivity). However, it should be noted that there are no available data on CBD efficacy in more relevant animal models of AUD, such as binge drinking models (Jeanblanc et al, 2018; Jeanblanc et al, 2019) or in models that use more chronic exposure to ethanol and behaviors linked to addiction (loss of control over intake, compulsive use of ethanol, increased motivation) (Meinhardt and Sommer, 2015). Thus, whether CBD is effective in animal models such as the postdependent state, in which rats drink ethanol for months and are exposed to ethanol vapors in order to induce dependence, is unknown.…”
Section: Cannabidiol For Reducing Alcohol Drinking Levelsmentioning
confidence: 99%
“…The biological action of the racemic drug Baclofen is known to reside with the active R(+)‐Baclofen 27 . We have recently demonstrated that R(+)‐Baclofen reduced alcohol intake, motivation to consume alcohol and alcohol relapse in a relevant animal model of binge drinking 28‐30 . Altogether these data demonstrated that R(+)‐Baclofen is the most interesting enantiomer; however, the data have been obtained in inbred mice and selectively bred mice and rats and no study compared the effect of R(+)‐Baclofen to those of RS(±)‐Baclofen and no data are available regarding interindividual responses.…”
Section: Introductionmentioning
confidence: 97%
“…While animal models are critical for experimental control over factors such as diet and ethanol (EtOH) exposure patterns, pharmacologically relevant BALs can be difficult to achieve (Li et al, 1979, but see Fabio et al, 2014; Jeanblanc et al, 2018). “Dependence,” objectively defined by the presence of withdrawal signs, has be induced with high doses of EtOH, typically via intragastric (French, 2001), intraperitoneal (Pascual et al, 2009, 2014), or vapor (Roberts et al, 2000; Vendruscolo and Roberts, 2014) exposure.…”
Section: Introductionmentioning
confidence: 99%